2013
DOI: 10.2528/pierb12112205
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Analysis of a Bridge Configured Winding Cage Induction Machine Using Finite Element Method

Abstract: Abstract-A 2D finite element electromagnetic model that permits the simulation of a cage induction machine, involving the effects of eddy currents and coupling the field equation with the stator fieldcircuit equation, has been presented in this paper. Transformation matrix has been derived to incorporate specialized stator winding scheme called the bridge configured winding (BCW) in the coupled field circuit equation. The bridge configured winding scheme is capable of producing controllable transverse force by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…His experimental findings have shown that using equalizing connections in the stator the UMP of an induction machine can be reduced by 25 times. The particular winding scheme has been called the bridge configured winding (BCW) scheme [52], and the currents flowing across this bridge are known as equalizing currents. It has shown the effect of equalizing currents (applied to the bridge) on the magnetic field coupled with rotor eccentricity.…”
Section: Reduction Of Umpmentioning
confidence: 99%
“…His experimental findings have shown that using equalizing connections in the stator the UMP of an induction machine can be reduced by 25 times. The particular winding scheme has been called the bridge configured winding (BCW) scheme [52], and the currents flowing across this bridge are known as equalizing currents. It has shown the effect of equalizing currents (applied to the bridge) on the magnetic field coupled with rotor eccentricity.…”
Section: Reduction Of Umpmentioning
confidence: 99%
“…This results in substantial cost savings for the inverter components and reduces inverter losses. Second, it is possible to passively provide corrective forces when the rotor is rotating eccentrically by simply short-circuiting the suspension terminals, a concept that has been explored in [17]. This is particularly useful in designs with mechanical bearings that require additional support when passing through critical speeds.…”
Section: Introductionmentioning
confidence: 98%
“…One group of these techniques can be differentiated by the fact that it provides separate suspension terminal connections which experience no motional-EMF when the rotor is centered [12]- [17], so-called "dual purpose no voltage" (DPNV) windings. DPNV windings have two key advantages over the other "dual purpose" approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Torque, stator current and ohmic losses have been calculated for all the models and compared with each other. A time stepping finite element method has been used in [13] for the electromagnetic analysis of a bridge configured based Induction machine. It can be observed that the frequency component of UMP due to eccentricity has good agreements with the analytical and experimental results.…”
Section: Introductionmentioning
confidence: 99%